PERAN GURU PAI DALAM PEMBENTUKAN AKHLAK SISWA PADA MASA PUBERTAS DI SMP TRI BHAKTI TEGALDLIMO - Mashuri, Imam; Ummah, Vina Rahmatul; Sanika, Ervin (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The aim to be achieved in this study is to determine the Role of Islamic Education Teachers in the Formation of Students’ Morals at Puberty at Tri Bhakti Tegaldlimo Middle School in the 2018/2019 Academic Year. To achieve the above objectives, the researcher used a qualitative research approach, with a descriptive type of research, in the form of data exposure to the location at Tri Bhakti Tegaldlimo Junior High School. The key instrument is the researcher himself. The data collection methods used are observation, interviews, and documentation. While the data analysis method used is descriptive qualitative analysis method. The data were analyzed by reducing the data, presenting the data, and drawing conclusions. It can be concluded that the role of the teacher in shaping the morals of students during puberty is as a guide, model (example) and advisor. The role of PAI teacher guidance at Tri Bhakti Tegaldlimo Middle School through habituation activities, namely: dhuha prayer in congregation, reading the al-Qur’an one week one juz, reviewing the book Risalatul Makhid, praying dhuhur in congregation, religious extracurricular hadrah, and khataman al Qur ‘ an. The role of Islamic education teachers as a model (example) with the example of teachers in increasing discipline, namely: time discipline, teachers come to school early and wait for students to arrive at the gate, discipline in dressing (appearance), teachers dress in Islamic, neat and polite, attitude discipline, act and speak polite words, make it a habit to say greetings when meeting. The role of PAI teachers as advisors at SMP Tri Bhakti Tegaldlimo is to provide advice and solutions to both students in general and students who have problems with approaches and provide solutions to always get closer to Allah SWT.